O DIREITO DE SER ADOTADO: A CONSTRUÇÃO DE UM NOVO DIREITO DA PERSONALIDADE (Reflection and Critique Law Magazine, 2024)
This article aims to investigate, from the perspective of the Brazilian legal system, the existence of an autonomous right to be adopted. This study also intended to verify whether children, as a consequence of that safeguard, may require efforts from the state to materialize the constitutional guarantee of family coexistence. The initial hypothesis, in the direction of the non-existence of the right, was not confirmed. The research identified, from the perspective of constitutional civil law, an autonomous right to be adopted, as an autonomous and deeper dimension of the guarantee to family coexistence provided for in art. 227 of the Brazilian Constitution. This theoretical framework allowed us to identify the eudaemonist affiliation as one of its vectors of the constitutional conception of the family and to expand its arc of incidence over the entire system. A new personality right was identified, based on individualities.